Who Is the Enemy? - Gil S. Epstein; Ira N. Gang (Institute for the Study of Labor (IZA), 2004)
We examine who benefits when there is a strong leader in place, and those who benefit when a situation lacks a proper leader. There are fractious terrorist groups who seek to serve the same people in common cause against a common enemy. The groups compete for rents obtained from the public by engaging in actions against the common enemy. We derive a condition under which the concerned parties, the terrorist groups and the local population upon whom the terrorist groups inflict their actions, benefit or lose in the two scenarios, and examine the consequences of counter-terrorist policy.
Keywords: D72; D71; D74; 330; terrorism; rent-seeking; all-pay auction; lottery; Politische Gewalt; Macht; Rent Seeking; Public Choice